Potential usefulness and clinical relevance of a novel left atrial filling index to estimate left ventricular filling pressures in patients with preserved left ventricular ejection fraction. (18th November 2019) - Braunauer, Kerstin; Düngen, Hans-Dirk; Belyavskiy, Evgeny; Aravind-Kumar, Radhakrishnan; Frydas, Athanasios; Kropf, Martin; Huang, Feiqiong; Marquez, Esteban; Tadic, Marijana; Osmanoglou, Engin; Edelmann, Frank; Tschöpe, Carsten; et al.
Abstract: Aims: The aim of this study was to examine the potential usefulness and clinical relevance of a novel left atrial (LA) filling index using 2D speckle-tracking transthoracic echocardiography to estimate left ventricular (LV) filling pressures in patients with preserved LV ejection fraction (LVEF). Methods and results: The LA filling index was calculated as the ratio of the mitral early-diastolic inflow peak velocity ( E ) over LA reservoir strain (i.e. E /LA strain ratio). This index showed a good diagnostic performance to determine elevated LV filling pressures in a test-cohort ( n  = 31) using invasive measurements of LV end-diastolic pressure (area under the curve 0.82, cut-off > 3.27 = sensitivity 83.3%, specificity 78.9%), which was confirmed in a validation-cohort (patients with cardiovascular risk factors; n  = 486) using the 2016 American Society of Echocardiography/European Association of Cardiovascular Imaging criteria (cut-off > 3.27 = sensitivity 88.1%, specificity 77.6%) and in a specificity-validation cohort (patients free of cardiovascular risk factors, n  = 120; cut-off > 3.27 = specificity 98.3%). Regarding the clinical relevance of the LA filling index, an elevated E /LA strain ratio (>3.27) was significantly associated with the risk of heart failure hospitalization at 2 years (odds ratio 4.3, 95% confidence interval 1.8–10.5), even adjusting this analysis by age, sex, renal failure, LV hypertrophy, or abnormal LV global longitudinal systolic strain. Conclusion: The findings from this study suggest that a novel LA filling index using 2D speckle-tracking echocardiography could be of potential usefulness and clinical relevance in estimating LV filling pressures in patients with preserved LVEF.